Role of Caveolae in the Development of Microvascular Dysfunction and Hyperglycemia in Type 2 Diabetes - Tian, Yanna; Fopiano, Katie Anne; Patel, Vijay S.; Feher, Attila; Bagi, Zsolt (Frontiers in Physiology, 2022)
In type 2 diabetes (T2D) microvascular dysfunction can interfere with tissue glucose uptake thereby contributing to the development of hyperglycemia. The cell membrane caveolae orchestrate signaling pathways that include microvascular control of tissue perfusion. In this study, we examined the role of caveolae in the regulation of microvascular vasomotor function under the condition of hyperglycemia in T2D patients and rodent models. Human coronary arterioles were obtained during cardiac surgery from T2D patients, with higher perioperative glucose levels, and from normoglycemic, nondiabetic controls. The coronary arteriole responses to pharmacological agonists bradykinin and acetylcholine were similar in T2D and non-diabetic patients, however exposure the isolated arteries to methyl-β-cyclodextrin (mβCD), an agent known to disrupt caveolae, reduced vasodilation to bradykinin selectively in T2D subjects and converted acetylcholine-induced vasoconstriction to dilation similarly in the two groups. Dilation to the vascular smooth muscle acting nitric oxide donor, sodium nitroprusside was not affected by mβCD in either group. Moreover, mβCD reduced endothelium-dependent arteriolar dilation to a greater extent in hyperglycemic and obese db/db mice than in the nondiabetic controls. Mechanistically, when fed a high-fat diet (HFD), caveolin-1 knockout mice, lacking caveolae, exhibited a significantly reduced endothelium-dependent arteriolar dilation, both ex vivo and in vivo, which was accompanied by significantly higher serum glucose levels, when compared to HFD fed wild type controls. Thus, in T2D arterioles the role of caveolae in regulating endothelium-dependent arteriole dilation is altered, which appears to maintain vasodilation and mitigate the extent of hyperglycemia. While caveolae play a unique role in microvascular vasomotor regulation, under the condition of hyperglycemia arterioles from T2D subjects appear to be more susceptible for caveolae disruption-associated vasomotor dysfunction and impaired glycemic control.